A mathematical programming model to select maintenance strategies in railway networks - Fecarotti, Claudia; Andrews, John; Pesenti, Raffaele (Reliability engineering & system safety, 2021)
This paper presents a nonlinear integer programming model to support the selection of maintenance strategies to implement on different segments of a railway network. Strategies are selected which collectively minimise the impact of sections’ conditions on service, given network availability and budget constraints. Different metrics related to the network topology, sections’ availability, service frequency, performance requirements and maintenance costs, are combined into a quantitative approach with a holistic view. The main contribution is to provide a simple yet effective modelling approach and solution method which are suitable for large networks and make use of standard solvers. Both an ad hoc heuristic solution and relaxation methods are developed, the latter enabling the quality of the heuristic solution to be estimated. The availability of railway lines is computed by exploiting the analogy with series–parallel networks. By varying the model parameters, a scenario analysis is performed to give insight into the influence of the system parameters on the selection of strategies, thus enabling more informed decisions. For its simple structure, the model is versatile to address similar problems arising in the maintenance of other types of networks, such as road and bridges networks, when deciding on the strategic allocation of maintenance efforts. •A nonlinear integer program is given to select maintenance strategies for railways.•A tailored heuristic enables fast solution to be found with standard solvers.•A tailored relaxation method enables the quality of the solution to be quantified.•Metrics of topology, availability, service, costs are combined in a holistic approach.•Effects of tracks redundancy, centrality, train frequency, availability are studied.